2022
DOI: 10.3389/fnins.2022.862873
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Gray Matter Volume in Tinnitus

Abstract: Tinnitus is the perception of sound without an external source. The flocculus (FL) and paraflocculus (PFL), which are small lobules of the cerebellum, have recently been implicated in its pathophysiology. In a previous study, the volume of the (P)FL-complex correlated with tinnitus severity in patients that had undergone cerebellopontine angle (CPA) tumor removal. In this study, the relation between tinnitus and gray matter volume (GMV) of the (P)FL-complex, GMV of the other cerebellar lobules and GMV of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…To date, structural neuroimaging studies using voxel-based morphometry (VBM) to investigate tinnitus have reported structural abnormalities in a variety of spatially distinct gray matter regions, including the auditory network (inferior colliculus, medial geniculate body, and primary or secondary auditory cortices), the default mode network (parietal cortices and prefrontal cortices), the salience network (anterior cingulate cortex and anterior insula), the limbic network (accumbens nucleus, amygdala, hippocampus, and parahippocampus), the visual network (primary or secondary visual cortices), the sensorimotor network (supplementary motor area), and the cerebellum [ 8 , 9 , 10 , 11 ]. In addition, VBM studies investigating tinnitus have also explored the relationships between these gray matter regions and clinical conditions that occur in conjunction with tinnitus, e.g., anxiety, depression, hearing loss, hyperacusis, and tinnitus burden [ 12 , 13 , 14 ]. However, the results have been highly inconsistent and sometimes contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…To date, structural neuroimaging studies using voxel-based morphometry (VBM) to investigate tinnitus have reported structural abnormalities in a variety of spatially distinct gray matter regions, including the auditory network (inferior colliculus, medial geniculate body, and primary or secondary auditory cortices), the default mode network (parietal cortices and prefrontal cortices), the salience network (anterior cingulate cortex and anterior insula), the limbic network (accumbens nucleus, amygdala, hippocampus, and parahippocampus), the visual network (primary or secondary visual cortices), the sensorimotor network (supplementary motor area), and the cerebellum [ 8 , 9 , 10 , 11 ]. In addition, VBM studies investigating tinnitus have also explored the relationships between these gray matter regions and clinical conditions that occur in conjunction with tinnitus, e.g., anxiety, depression, hearing loss, hyperacusis, and tinnitus burden [ 12 , 13 , 14 ]. However, the results have been highly inconsistent and sometimes contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…The loudness of the tinnitus varies by ocular movements. Atrophy of the flocculus on the surgical side has been suggested to modulate tinnitus [ 15 , 16 ]. Functional MRI revealed that tinnitus is associated with activities of the Heschl’s gyrus, angular gyrus, cerebellar, and limbic system [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, here we have intentionally focused particularly on the hippocampal system, to consider the nature of tinnitus as a persistent memory, a cognitive process in which the hippocampus/PHG are most‐commonly implicated, rather than discussing in detail other mechanisms behind tinnitus that are undoubtedly relevant. These mechanisms have implicated several other brain regions beyond the hippocampus and auditory system, including nucleus accumbens, ventromedial prefrontal cortex, thalamic reticular nucleus, middle frontal gyrus, fornix, and precuneus (Leaver et al, 2011 ; Rauschecker et al, 2010 ; Rauschecker et al, 2015 ; Rosemann & Rauschecker, 2022 ; Rosemann & Rauschecker, 2023a ; Rosemann & Rauschecker, 2023b ), cerebellum (Bauer et al, 2013 ; Mennink et al, 2022 ), insula (Chen et al, 2023 ; Lenhardt et al, 2008 ), and cingulate cortex (Chen, Liu, et al, 2018 ; Golm et al, 2013 ). These structures likely play roles in tinnitus that are not necessarily mutually exclusive, including—but not limited to—those involved in persistence of a memory trace, gating of pathological auditory activity and emotional responses to a chronic phantom percept.…”
Section: A Model For Persistent Tinnitusmentioning
confidence: 99%